Structural Determinants for Small-Molecule Activation of Skeletal Muscle AMPK α2β2γ1 by the Glucose Importagog SC4. Issue 6 (21st June 2018) - Ngoei, Kevin R.W.; Langendorf, Christopher G.; Ling, Naomi X.Y.; Hoque, Ashfaqul; Varghese, Swapna; Camerino, Michelle A.; Walker, Scott R.; Bozikis, Ylva E.; Dite, Toby A.; Ovens, Ashley J.; Smiles, William J.; Jacobs, Roxane; et al.
Summary: The AMP-activated protein kinase (AMPK) αβγ heterotrimer regulates cellular energy homeostasis with tissue-specific isoform distribution. Small-molecule activation of skeletal muscle α2β2 AMPK complexes may prove a valuable treatment strategy for type 2 diabetes and insulin resistance. Herein, we report the small-molecule SC4 is a potent, direct AMPK activator that preferentially activates α2 complexes and stimulates skeletal muscle glucose uptake. In parallel with the term secretagog, we propose "importagog" to define a substance that induces or augments cellular uptake of another substance. Three-dimensional structures of the glucose importagog SC4 bound to activated α2β2γ1 and α2β1γ1 complexes reveal binding determinants, in particular a key interaction between the SC4 imidazopyridine 4′-nitrogen and β2-Asp111, which provide a design paradigm for β2-AMPK therapeutics. The α2β2γ1/SC4 structure reveals an interaction between a β2 N-terminal α helix and the α2 autoinhibitory domain. Our results provide a structure-function guide to accelerate development of potent, but importantly tissue-specific, β2-AMPK therapeutics. Graphical Abstract: Highlights: SC4 is a potent allosteric activator of AMPK complexes containing the β2 isoform SC4 stimulates β2-AMPK in cells, and glucose uptake by isolated skeletal muscle Binding to β2-AMPK is mediated by 4′-nitrogen in the SC4 core and β2 residue Asp111 We identified an interaction between β2 N terminus and AMPK autoinhibitory domain Abstract : Therapeutic activation of the metabolic regulator AMPK in skeletal muscle is a validated strategy to combat type 2 diabetes. Ngoei et al. have solved the crystal structure of the activator SC4 complexed to a skeletal muscle AMPK isoform, identifying important binding determinants that will advance development of AMPK-targeting therapeutics.